Dietary Energy Levels Affect Carbohydrate Metabolism-Related Bacteria and Improve Meat Quality in the Longissimus Thoracis Muscle of Yak (Bos grunniens) - Du, Mei; Yang, Chao; Liang, Zeyi; Zhang, Jianbo; Yang, Yayuan; Ahmad, Anum Ali; Yan, Ping; Ding, Xuezhi (Frontiers in Veterinary Science, 2021)
The effects of different dietary energy levels on the ruminal bacterial population, selected meat quality indices and their relationship in yak longissimus thoracis (LT) muscle were assessed in this study. Fifteen castrated yaks were randomly assigned to three groups with low- (NEg: 5.5MJ/Kg, LE), medium- (NEg: 6.2MJ/Kg, ME) and high- (NEg: 6.9MJ/Kg, HE) dietary energy levels and occurred in the cold season (March to May). All yaks from each treatment group were humanely slaughtered and sampled on the day of completion of their feeding treatment. The results showed that water content and crude fat levels of LT muscle were markedly elevated in the HE group (P < 0.05), while the shear force was drastically reduced (P = 0.001). Methionine, aspartic acid, and glycine levels in LT muscle were higher in the LE group compared with the ME and HE groups (P < 0.05). The glutamic acid level in the ME group was greater in comparison to the LE and HE groups (P < 0.05), while histidine level in the ME group was higher than in the HE group (P < 0.05). Additionally, the HE diet significantly elevated (P < 0.05) the abundance of carbohydrate metabolism associated bacteria including Prevotella_1, Lachnospiraceae_NK4A136_group, U29_B03, Ruminiclostridium_6 and Ruminococcaceae_UCG_013 in the rumen. The results of Spearman’s rank correlation analysis showed that the abundance of uncultured_bacterium_f_vadinBE97 and uncultured_bacterium_f_Lachnospiraceae showed a significant influence on the indicator of IMF and SF. In conclusion, high dietary energy level improved meat quality in the LT muscle of yak mainly by increasing the relative abundance of ruminal amylolytic bacteria to provide substrates for fatty acid synthesis.